2007
DOI: 10.1097/mlg.0b013e31811ff906
|View full text |Cite
|
Sign up to set email alerts
|

Laryngopharyngeal Abnormalities in Hospitalized Patients With Dysphagia

Abstract: Hospitalized patients with dysphagia are at high risk for LP abnormalities, particularly if they have been intubated, and may benefit from either 1) an initial joint examination by the SLP and otolaryngologist or 2) an otolaryngologist's review of the recorded examination conducted by the SLP. Such otolaryngology involvement could identify airway stenosis patients at an earlier stage, initiate granuloma treatment sooner, enable earlier biopsy of unexpected lesions, and allow follow-up of mucosal and neuromuscu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 10 publications
0
13
0
Order By: Relevance
“…While determining causation is outside the scope of the current study, some have reported structural and mechanical alterations to the upper airway following extubation in those patients with dysphagia [16,20]. In addition, various intubation techniques and induction medication can either positively or negatively affect protective airway reflexes [21].…”
Section: Discussionmentioning
confidence: 99%
“…While determining causation is outside the scope of the current study, some have reported structural and mechanical alterations to the upper airway following extubation in those patients with dysphagia [16,20]. In addition, various intubation techniques and induction medication can either positively or negatively affect protective airway reflexes [21].…”
Section: Discussionmentioning
confidence: 99%
“…13 Another study found that for every additional 12 hours of intubation in cardiovascular surgery patients, there was a 1.93 increased risk of dysphagia. 21 In anticipation of laryngeal injury, 1 study investigated an intervention to prevent laryngeal edema by injecting patients with methylprednisolone 12 hours before planned extubation and found that it reduced significantly more cases of laryngeal edema than the placebo group. [15][16][17][18][19] Other risk factors have been reported, although there is considerable contrast across studies: age, diabetes, surgery type, reduced functional status pre-intubation, perioperative transesophageal echocardiograms, and tracheostomy.…”
Section: Risk Factors and Outcomes Of Intubationmentioning
confidence: 99%
“…The primary function of the larynx is sphincteric protection of the airway against ingress of digestive tract contents, and the principal mechanism by which this is achieved is reflexive closure of the true vocal folds during swallowing . Vocal palsy impairs glottic closure, and this is known to lead to dysphagia and aspiration in 20%‐40% of the affected patients …”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4] Vocal palsy impairs glottic closure, and this is known to lead to dysphagia and aspiration in 20%-40% of the affected patients. [5][6][7][8][9] There are a wide range of surgical procedures that place normally functioning laryngeal nerves at risk of injury, which in turn places the patient at risk of post-operative dysphonia, dysphagia, and less commonly, airway compromise. 5,[10][11][12][13][14] Thyroidectomy is the commonest of these procedures (Figure 1).…”
Section: Introductionmentioning
confidence: 99%